Analysis of the impact of communication between the participants of a construction project on its completion time and cost - Kania, Ewelina; Śladowski, Grzegorz; Radziszewska-Zielina, Elżbieta; Sroka, Bartłomiej (Archives of civil engineering, 2022)
Communication and information flowduring construction project execution is often discussed in the literature. Numerous scholars note the presence of problems with communication and information flow and highlight that these problems also affect construction project completion time and cost. The vast majority of studies on the impact of communication on construction project completion time and cost takes on a qualitative character and there is a lack of quantitative analyses of this subject. To address these deficiencies, the authors of this paper propose a quantitative approach to assessing communication between construction project participants in the aspect of its impact on said project’s completion time and cost. The authors used meta-network theory to model and analyse the problem, as it can fully depict the problem’s complexity. The method proposed allows for dynamic identification of key information flow paths between project participants, which determine its performance in an essential way. The proposed approach can support decision-makers in effective management of communication between a construction project’s participants, which has a positive carryover to achieving planned project goals. The method was tested on a real-world development project that featured the construction of a housing complex in Katowice, Poland.